Gas-Liquid Flows in Vertical Annular Channels - Bilgin, Egemen Orhan (Université d'Ottawa | University of Ottawa, 2026)
Experimental and computational studies of air bubbles rising in stagnant and flowing water in vertical annular channels for the full range of eccentricity (e) were performed. The experiments were conducted in a specially designed experimental facility and two video cameras were used to record the flow from two directions perpendicular to each other. Analysis of the videos and use of computer-aided-design (CAD) software provided measurements of the velocity, length, shape, volume and angle of wrap of Taylor bubbles in stagnant water for 0 ≤ e ≤ 1. The bubble velocity increased with increasing eccentricity from the concentric value (e = 0), peaked for e ≈ 0.2 - 0.3 and then decreased with further increasing eccentricity, reaching a minimum value for e = 1. The maximum angle of wrap decreased monotonically with increasing eccentricity in its full range. The same observations were also made in our numerical simulations. On the other hand, the bubble length and volume were essentially insensitive to eccentricity. Isolated Taylor bubbles in upward flowing water were found to be slimmer and had a smaller maximum angle of wrap than bubbles with comparable lengths rising in stagnant water. Four regimes were identified visually in upwards air-water flows in annular channels, namely, bubbly, cap-bubbly, slug and churn flows. A flow regime map was constructed for the full range of eccentricity. The transition regions of the map were shifted with changes in eccentricity in the range e = 0.3 - 0.7. Oscillatory cross-flows, attributed to gap vortex streets, were visually identified in the recordings of bubbly, cap-bubbly and slug flow regimes for e = 0.5 and 0.7. The numerical simulations also provided evidence for the presence of gap vortex streets in gas-liquid flows in highly eccentric annular channels. These vortex streets are deemed to be a main source of the eccentricity effects.
Keywords: eccentric annular channel; flow regimes; gap instability; Taylor bubbles